Implementation of the Pawongan Values of Tri Hita Karana Teachings to Strengthen Diversity in SMA Katolik Kesuma Mataram - Wadi, Hairil; Junaidi, Eka; Sutajaya, I Made; Suja, I Wayan; Made Astawa, Ida Bagus (Universitas Tanjungpura, 2024)
This research aims to examine the implementation of the Pawongan Values of Tri Hita Karana Teachings to Strengthen Diversity at Kesuma Mataram Catholic High School. The research method uses a qualitative descriptive method approach, with data collection techniques through interviews, observation and documentation. Data analysis follows the Miles and Huberman model of qualitative analysis with stages of data reduction, data presentation, and drawing conclusions. The results of the research show that the Pawongan value of the Tri Hita Karana teachings is implemented and strengthens diversity at Kesuma Mataran Catholic High School, in various forms of activities such as social service, social communication, joint celebration of religious holidays, imtak programs, choirs, financial assistance, giving gifts, donations to requiring.